2022
DOI: 10.1369/00221554221116936
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Histological Assessment of Prostate Specimens in the Three-dimensional Space by Hydrophilic Tissue Clearing and Confocal Microscopy

Abstract: Microscopic examination of biopsied and resected prostatic specimens is the mainstay in the diagnosis of prostate cancer. However, conventional analysis of hematoxylin and eosin (H&E)-stained tissue is time-consuming and offers limited two-dimensional (2D) information. In the current study, we devised a method—termed Prostate Rapid Optical examination for cancer STATus (proSTAT)—for rapid screening of prostate cancer using high-resolution 2D and three-dimensional (3D) confocal images obtained after hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The treated sciatic nerves were harvested at 7 days postoperation. Additional fluorescent dye was added to stain the plasma membrane and nucleus, and the tissues were optically cleared in preparation for high‐resolution 3D confocal imaging 35,36 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The treated sciatic nerves were harvested at 7 days postoperation. Additional fluorescent dye was added to stain the plasma membrane and nucleus, and the tissues were optically cleared in preparation for high‐resolution 3D confocal imaging 35,36 …”
Section: Resultsmentioning
confidence: 99%
“…Additional fluorescent dye was added to stain the plasma membrane and nucleus, and the tissues were optically cleared in preparation for high-resolution 3D confocal imaging. 35,36 One day after treatment, more CM-DiI-labeled cells were detected in the group that received SC spheroids than in the group that received SC suspensions (Figure 7a), suggesting that the acute retention rate of injected cells could be improved when cells were delivered as 3D spheroids. Seven days after cell administration, only a limited number of CM-DiI-positive cells were detected in the retrieved sciatic nerves treated with SC suspensions, revealing significant cell loss (Figure 7a and Supplementary Video 1).…”
Section: The Secretome Of Sc Spheroids Recruits Macrophagesmentioning
confidence: 99%
“…Regarding interobserver agreement between pathologists for TPS (Table 3 ), we found that the agreement of TPS in IF images after HDR processing was ameliorated, but still had not as much as the agreement in IHC, possibly because IF images were less frequently used in routine training of pathologists. Except for additional training and more clinical cases, we can also apply pseudo-H&E and IHC processing to transform the color domain of fluorescent images, which will help pathologists become more familiar with fluorescent images to evaluate the biomarker expression patterns in a familiar format 45 .…”
Section: Discussionmentioning
confidence: 99%